PP.39.21: ANGIOTENSIN FORMATION IN HEALTHY HUMAN VS. MICE KIDNEYS. FOCUSING ON CLASSICAL AND ALTERNATIVE PATHWAYS. (June 2015) - Kaltenecker, C.; Domenig, O.; Kopecky, C.; Antlanger, M.; Poglitsch, M.; Kain, R.; Säemann, M.D.; Kovarik, J.J.
Abstract : Objective: The renin-angiotensin system (RAS) is a key regulator of blood pressure, fluid and electrolyte homeostasis and is involved in tissue remodeling. Kidney RAS dysregulation in disease conditions has been investigated in various animal models and human studies, indicating that substantial species-specific differences exist. Hence, in order to understand both, RAS metabolism, as well as the physiological consequences of RAS blockade at the tissue level, characterization of intrarenal RAS biology of healthy humans is essential. Design and method: Kidneys of living donors – treated without RAS blockade, angiotensin converting enzyme inhibitor (ACEi) or angiotensin receptor blocker (ARB) – were biopsied pre-transplant and tissue samples were obtained. Accordingly, kidneys from 12-week old female C57BL/6 mice were snap-frozen immediately after harvesting. Homogenates of the respective tissue samples were used for measuring RAS enzyme activities by a novel mass-spectrometry based approach. Selective enzyme inhibitors were employed to discern ACE- and chymase-dependent Ang II formation. Renal expression of these RAS enzymes was determined by immunohistochemical staining of biopsy tissue. Results: Endogenous Ang II generation in murine kidneys was completely ACE-dependent. The contribution of ACE to Ang II formation was lower in subjects receiving ACEi therapy compared to those receiving no RAS blockade or ARB treatment indicating high ACE-independent enzyme activity. Interestingly, no difference in ACE and chymase expression between the groups was observed. Conclusions: Our data imply that in subjects receiving ACEi therapy, ACE-independent enzymes significantly contribute to local Ang II formation. These results shed new light on the intrarenal effects of ACEis in humans and may have considerable implications for current and future RAS blocking therapies.